ANALISIS STRATEGI NON-KOGNITIF DALAM PENGEMBANGAN KEPERCAYAAN DIRI SISWA SEKOLAH DASAR - Yuni Lutfiyah; Elan; Anggit Merliana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Self-confidence is an essential aspect of the psychosocial development process in elementary school students. Children with self-confidence tend to show active engagement in learning activities, courage to try new things, and the ability to express themselves. However, the development of self-confidence in elementary schools has not received adequate attention in formal learning, as academic and cognitive approaches remain dominant. This article is a literature review that aims to examine theories and non-cognitive strategies for developing self-confidence in elementary school students. By reviewing more than 20 scientific articles from national and international journals, it was found that strategies based on art, games, group work, and self-reflection have a positive impact on shaping and strengthening children's self-confidence. This literature review also emphasizes the importance of comprehensive support from various educational components, such as integration into the curriculum, strengthening teacher competencies through training, and creating a school culture that supports character development. Therefore, self- confidence should not be considered merely a byproduct of the learning process but should be established as one of the primary goals of learning, designed consciously, structurally, and systematically within the elementary school environment.